2012
DOI: 10.1093/ndt/gfr754
|View full text |Cite
|
Sign up to set email alerts
|

The balance of beneficial and deleterious effects of hypoxia-inducible factor activation by prolyl hydroxylase inhibitor in rat remnant kidney depends on the timing of administration

Abstract: HIF-α activation by PHD inhibitor L-Mim has dual roles in the development of CKD in the rat RK model depending on the timing of the administration and possibly the activated isoform of HIF-α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 37 publications
6
78
1
1
Order By: Relevance
“…Simultaneously, there was transient HIF-␣ activation in the remnant kidney of rats at the early stage following subtotal nephrectomy, which also peaked at weeks 4 and 6. L-Mim administered in later stages reactivated HIF-␣ and ameliorated the progression of CKD and renal interstitial fibrosis (56,57). In the present study, we found the abundance of a miRNA, miR-29c, which is known to suppress the expression of extracellular matrix genes (22), was decreased in the rat remnant kidney model as well as in human kidneys with TIF from IgA nephropathy patients.…”
supporting
confidence: 58%
“…Simultaneously, there was transient HIF-␣ activation in the remnant kidney of rats at the early stage following subtotal nephrectomy, which also peaked at weeks 4 and 6. L-Mim administered in later stages reactivated HIF-␣ and ameliorated the progression of CKD and renal interstitial fibrosis (56,57). In the present study, we found the abundance of a miRNA, miR-29c, which is known to suppress the expression of extracellular matrix genes (22), was decreased in the rat remnant kidney model as well as in human kidneys with TIF from IgA nephropathy patients.…”
supporting
confidence: 58%
“…Recent data using the remnant kidney model furthermore indicate that renoprotection is dependent on the timing of pharmacologic HIF activation. 28 While it has been suggested that HIF promotes progression of CKD by increasing the expression of profibrotic factors and by facilitating epithelial dedifferentiation, 24 the mechanisms underlying renoprotection are likely to involve multiple signaling pathways and metabolic changes, which include HIFinduced expression of cytoprotective genes; reprogramming of glucose, energy, and adenosine metabolism; beneficial effects on mitochondrial O 2 utilization, renal _ VO 2 , and mitochondrial ROS production; enhanced ROS scavenging; suppression of renal inflammation; and maintenance of vascular health and integrity (Figure 1). 23,27,29,30 Given that the regulation of the PHD/HIF axis and its downstream targets is cell type dependent and involves multiple feedback loops including changes in the epigenome, it is likely that the mechanisms of HIF-mediated cytoprotection differ between acute and chronic hypoxic conditions.…”
Section: Therapeutic Opportunities Beyond Renal Anemiamentioning
confidence: 99%
“…However, regarding their effects in reducing cardiovascular events and slowing the progression of the renal disease, no data are still available from human studies. Yu et al [22] showed that the administration of PHD inhibitors in a more advanced stage of CKD in the rat reduced renal fibrosis and protected renal function, whereas the administration in an early stage of CKD promoted renal fibrosis and exacerbated renal dysfunction. In another strategy to induce EPO production, the hydrodynamic gene transfer of a plasmid encoding for EPO in a rat model overexpressing TGF-β showed that this therapy increased Hb levels but had no effect on kidney fibrosis or function [74].…”
Section: Erythropoiesis-stimulating Agents In Ckd-anemiamentioning
confidence: 99%
“…It was reported that HIF-α activation in CKD rats presents dynamic changes, as it is activated in early CKD stages and suppressed in the moderate and end-stage of CKD [95]. Thus, the administration of PHD inhibitors may improve renal function in more advanced stages of CKD, while in earlier stages, the PHD inhibitors may increase renal fibrosis due to upregulation of the HIF-1α subunit [22].…”
Section: Hif System In the Hyporesponsiveness To Erythropoiesis-stimumentioning
confidence: 99%
See 1 more Smart Citation